CUMULATIVE IMPACT OF THE MINING INDUSTRY AND AGRICULTURE ON THE HYDROGEOCHEMICAL STATE OF THE TERRITORY (BASED ON THE EXAMPLE OF SOUTHERN KRYVBAS) - PIGULEVSKIY, Petro; DOVBNICH, Mykhailo; TIAPKIN, Oleh; MEDVEDIEVA, Olha; ANISIMOVA, Larysa (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Southern Kryvbas is one of the most industrially loaded territories in southeastern Ukraine. Manmade changes in the environment are becoming irreversible, affecting the ecosystem, especially the soils. The presented studies conducted a general analysis of the mobility of the main chemical elements that pollute the territory adjacent to mining enterprises as a result of agricultural activities and determine the degree of influence of the migration of relevant chemical elements on the geochemical state of soils, surface, and groundwater.Methods. To determine the degree and nature of manmade changes in the hydrogeochemical state of southern Kryvbas, a comparativestatistical analysis method was applied to generalize the results of previous hydrogeochemical studies of the impact of the mining industry and agriculture on the main components of the environment.Results. As a result of the joint action of industrial and agricultural activity factors over a long period, new stable natural-manmade geosystems have formed. The main pollutants of soils, groundwater, surface waters, and bottom sediments in mining regions are waste from the mining industry and agricultural fertilizers. The analysis of the main pollutants shows that the contaminating components are practically identical. This leads to an unjustified exaggeration of the results of mining activities in the overall pollution of adjacent agricultural territories. It has been shown that it is insufficient to rely solely on geochemical data to distinguish the hazardous impact of the mining industry and agricultural complex on the pollution of a particular region. Additional spatial-temporal geological-geophysical studies of both the sources and pathways of specific types of pollution are necessary. At the same time, the structural-tectonic features play a decisive role in assessing the hydrogeoecological state of the research territory, for the parameterization of which the use of known concepts about the systems of Precambrian faults established based on a comprehensive set of geological-geophysical data is required.Conclusions. It has been concluded that the migration of specific chemical elements has a significant impact on the geochemical state of soils, surface, and groundwater. The presence of spatial-depth geological-geophysical information about the features of tectonic (fault-block) structure is one of the foundations for the development of a methodology for distinguishing the elements of the hazardous impact of the mining industry and agricultural complex in the formation of the overall hydrogeochemical state of a specific region.
Keywords: mining industry waste; hydrogeochemistry; fertilizers; mobile forms of chemical elements; geological-geophysical information; tectonic structure; crustal faults; chemical contamination of soils, surface and groundwater